(untitled) (Journal of Social Sciences Review, 2025)
Positive Psychology-based interventions can help individuals build a positive self-concept and improve it by increasing positive emotions. Adolescents suffer various issues as they are in a critical period for the development of self-esteem. During this stage, Positive psychology-based interventions can play a significant role in building and enhancing self-worth and self-concept. Gratitude-based interventions develop a positive self-image of adolescents and help them cope with the challenges that adolescents face during this transitional stage. The goal of this study was to develop an effective intervention for promoting gratitude by enhancing self-esteem among adolescents from from17-19 years (M =17.36, SD =.52). Pre-post experimental research design with the intervention was used wherein pre and post-assessments were conducted on both the experimental and control group each consisting (n=100) participants. College students from both private and public institutions were included. Responses were collected using gratitude, self-esteem, and moral disengagement questionnaires. In this study, counting blessing intervention was given to the experimental group for a period of two weeks, followed by a post-assessment. Analysis was conducted by using SPSS 23. Study results showed no change in the relationship between pre-and post-tests for the control group regarding the correlation between person-product moment. However, there is a change in the relationship between the pre and post-test for the experimental group. Results from a two-way analysis of variance indicated a substantial increase in the post-test of the experimental group for gratitude and a decrease in aggression and moral disengagement. Results of the study revealed that participants of the experimental group reported feeling more positive after performing counting blessing intervention. The study concluded that gratitude intervention is associated with enhancing gratitude and self-esteem among adolescents by decreasing the level of moral disengagement.